ANALISIS DAN PERANCANGAN SISTEM INFORMASI ADMINISTRASI DISPOSISI SURAT BERBASIS WEB PADA DINAS PEKERJAAN UMUM DAN PERUMAHAN RAKYAT PROVINSI JAMBI - Ericson, Ericson; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2018)
Development of today's technology lead government agencies to modernize public administration in order to accelerate and facilitate the completion of documents and government agencies, the administration is one important requirement in a government agency or organization in realizing kepemerintahaan good, one that is not supported by the system administration, namely the Department of Public Works and Public Housing Jambi, there are still some problems related to the administration of the letter, especially incoming mail as well as the disposition of the Head of Department to the units associated sometimes not until, with administration information system disposition web-based mail at the Department of Public Works and Public Housing Jambi this research resulted in the design and analysis system that describes the disposition letter with system development model used is the Unified Modeling Language use case diagram,